1998
DOI: 10.1006/viro.1998.9508
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A Virus Lacking the NS1 Gene Replicates in Interferon-Deficient Systems

Abstract: The NS1 protein is the only nonstructural protein encoded by influenza A virus. It has been proposed that the NS1 performs several regulatory functions during the viral replication cycle, including the regulation of synthesis, transport, splicing, and translation of mRNAs. Through the use of reverse genetics, a viable transfectant influenza A virus (delNS1) which lacks the NS1 gene has been generated. Our results indicate that the NS1 of influenza A virus is an auxiliary (virulence) factor which plays a crucia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
834
2
9

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 917 publications
(877 citation statements)
references
References 32 publications
32
834
2
9
Order By: Relevance
“…We next considered the possibility that hvPR8 might carry mutations that lead to particularly strong suppression of the antiviral IFN response in infected cells. Enhanced virulence of human and avian FLUAV strains has been attributed to the NS1 gene that is known to suppress IFN synthesis in virus-infected cells (5,16,18,19). We found that both hvPR8 and standard lvPR8 suppressed early IFN synthesis in lungs of infected mice very strongly, indicating that the NS1 proteins of both viruses act as functional IFN antagonists.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…We next considered the possibility that hvPR8 might carry mutations that lead to particularly strong suppression of the antiviral IFN response in infected cells. Enhanced virulence of human and avian FLUAV strains has been attributed to the NS1 gene that is known to suppress IFN synthesis in virus-infected cells (5,16,18,19). We found that both hvPR8 and standard lvPR8 suppressed early IFN synthesis in lungs of infected mice very strongly, indicating that the NS1 proteins of both viruses act as functional IFN antagonists.…”
Section: Discussionmentioning
confidence: 71%
“…Because it was possible that the high virulence of hvPR8 in Mx1 ϩ/ϩ mice resulted from extraordinary suppression of virus-induced IFN synthesis, we determined the capacity of hvPR8 and lvPR8 to induce IFN-␤ in cell culture and lungs of infected mice. As positive control for these experiments, we used PR8delNS1, a NS1-deficient PR8 mutant virus which is a potent IFN inducer (16). To avoid complications resulting from differences in virus growth kinetics, the mice were infected with a high dose of virus (10 5 pfu) and killed 10 h later.…”
Section: Ifn Protects Against Hvpr8 In Mx1mentioning
confidence: 99%
“…NS1 encoded by inf luenza A virus was among those first selected because it is encoded by an overlapping gene and inf luences virulence and virus accumulation but is not essential for viral replication (33), which are common features of many known viral silencing suppressors such as the nodaviral B2 and plant viral 2b proteins (12,16,34). We found that NS1 protein expressed from a cotransfected plasmid indeed rescued GFP expression from pFR1gfp in Drosophila cells (Fig.…”
Section: Identification Of Mammalian Viral Proteins That Suppress Thementioning
confidence: 72%
“…NS1 deletion or truncation attenuates an influenza virus by reducing its ability to antagonize the type I IFN response [28]. It was hypothesized that this class of mutant viruses would elicit robust adaptive immune responses, despite attenuated replication, because restraints on the early innate response would be relaxed.…”
Section: Discussionmentioning
confidence: 99%